PERTANGGUNGJAWABAN KORPORASI TERHADAP TINDAK PIDANA PENCEMARAN LINGKUNGAN PERSPEKTIF HUKUM POSITIF DAN HUKUM PIDANA ISLAM (ANALISIS PUTUSAN NOMOR : 333/Pid.B/LH/2019/PN.Ckr) - Achmad Fadhilatur Rahman (CLEAR: Criminal Law Review, 2025)
Accountability plays a crucial role in fostering awareness to prevent individuals from committing unlawful acts that may harm the public. This study is particularly noteworthy as it examines a judicial decision based on the third alternative indictment of the public prosecutor, where the relevant provision does not stipulate a minimum fine. Consequently, judges may impose penalties of a very minimal amount. The research focuses on three aspects: (1) A review of corporate liability for environmental pollution offenses under positive law, as reflected in Decision No. 333/Pid.B/LH/2019/PN.Ckr; (2) An examination of the same case from the perspective of Islamic criminal law; and (3) A comparative analysis between the two legal frameworks. The objective is to understand and compare corporate liability in environmental pollution cases under both systems based on the aforementioned ruling. This normative legal research adopts statutory and case approaches, utilizing primary, secondary, and tertiary legal materials. Data collection was conducted through literature review, document analysis, and legal dictionaries, while data analysis followed Miles and Huberman’s theory—comprising data collection, reduction, presentation, and conclusion—validated through triangulation. Findings indicate that, under positive law, the absence of a minimum fine in Article 104 of the Environmental Protection and Management Law (PPLH) undermines deterrence, as judges may impose insufficiently punitive sanctions. In contrast, Islamic criminal law prescribes imprisonment and exile for environmental pollution offenders. The study concludes that the effectiveness of sentencing is better aligned with the positive law framework, provided that a minimum fine requirement is incorporated into Article 104 of the PPLH Law. Pertanggungjawaban memiliki peran penting dalam menumbuhkan kesadaran agar seseorang tidak melakukan perbuatan melawan hukum yang merugikan masyarakat. Penelitian ini menarik karena menyoroti putusan hakim berdasarkan dakwaan alternatif ketiga penuntut umum, di mana pasalnya tidak menetapkan batas minimal pidana denda. Akibatnya, hakim dapat menjatuhkan denda dalam jumlah sangat kecil. Fokus penelitian mencakup: (1) Tinjauan hukum positif tentang pertanggungjawaban korporasi atas tindak pidana pencemaran lingkungan dalam putusan No. 333/Pid.B/LH/2019/PN.Ckr; (2) Tinjauan hukum pidana Islam atas kasus yang sama; dan (3) Perbandingan keduanya. Tujuan penelitian adalah memahami dan membandingkan perspektif hukum positif dan hukum pidana Islam terkait pertanggungjawaban korporasi berdasarkan putusan tersebut. Metode yang digunakan adalah penelitian normatif dengan pendekatan undang-undang dan kasus. Sumber hukum meliputi bahan primer, sekunder, dan tersier, dengan teknik pengumpulan data melalui studi pustaka, studi dokumen, dan kamus hukum.Analisis data mengikuti teori Miles dan Huberman, meliputi ngumpulan, reduksi, penyajian, dan penarikan kesimpulan, serta uji keabsahan dengan triangulasi. Hasil penelitian menunjukkan bahwa menurut hukum positif, penjatuhan pidana denda tanpa batas minimal tidak memberikan efek jera, sebagaimana terlihat pada Pasal 104 UU PPLH. Sementara itu, hukum pidana Islam memandang pelaku pencemaran lingkungan layak dijatuhi pidana penjara dan pengasingan. Peneliti menyimpulkan bahwa efektivitas putusan lebih sesuai dengan konsep hukum positif, dengan catatan penambahan ketentuan batas minimal denda pada Pasal 104 UU PPLH.